Originally Posted by

**Grillakis** Q: Find f(1), f(2), f(3), f(4), and f(5) if f(n) is defined recursively by f(0) = 3

and for n = 0, 1, 2, …

a.) f(n + 1) = -2f(n)

__________________________________________________ _______________

a.)

f(n + 1) = -2f(n)

f(0 + 1) = -2f(0)

f(1) = -2(3)

f(1) = - 6

f(n + 1) = -2f(n)

f(1 + 1) = -2f(1)

f(2) = -2(-6)

f(2) = 12

f(n + 1) = -2f(n)

f(2 + 1) = -2f(2)

f(3) = -2(12)

f(3) = -24

f(n + 1) = -2f(n)

f(3 + 1) = -2f(3)

f(4) = -2(-24)

f(4) = 48

f(n + 1) = -2f(n)

f(4 + 1) = -2f(4)

f(5) = -2(48)

f(5) = -96